A Bibliometric Study of Research-Technology Management, 1998–2017: An analysis of 20 years of RTM articles offers a perspective on trends and evolutions in the journal's content and in the field of innovation management. Issue 1 (2nd January 2019) - Shum, Vanessa; Park, Andrew; Maine, Elicia; Pitt, Leyland F.
Abstract : Overview: A bibliometric study of Research-Technology Management ( RTM ), conducted for the 20-year period 1998–2017, examined citations, authors, industry sectors, and topics for 550 articles published during the period to identify relevant trends. Along with providing guidance to prospective RTM authors and reviewers regarding the journal's areas of focus, the study also provides an indication of the evolution in the topics most relevant to innovation and technology management practitioners. Our findings show RTM 's growing global reach—the past 20 years have seen a significant increase in the number of articles from European academic authors. The analysis suggests that scholars and practitioners look to RTM primarily for thought leadership about knowledge and portfolio management and new product development; the journal's most-cited articles are in the field of new product development. Further, while the majority of articles are relevant across industry sectors, we find a growing proportion of articles about information technology.